Strategi Dinas Pariwisata dalam pengembangan pariwisata Kota Surakarta di masa pandemi Covid-19 - Erna Okta Amelia; Joko Pramono; Damayanti Suhita (Universitas Merdeka Malang, 2022)
Tourism is one of the largest economic generating sectors in the world. Tourism development is a series of activities that create integration in the use of various resources and integrate all forms of aspects outside of tourism with the aim of making tourism even better. This research is a descriptive research using qualitative methods. As we know that the COVID-19 pandemic has affected almost all lines of life. Tourism and the economy have been badly affected by the COVID- 19 pandemic. Therefore, a strategy is needed in the development of tourism in Surakarta City during the COVID-19 pandemic. The formulation of tourism development strategies in this study uses a SWOT analysis technique. Before designing a strategy using a SWOT analysis, he explained the condition of tourism during the COVID-19 pandemic. SWOT analysis is used to identify Strengths, Weaknesses, Opportunities and Threats on the research object. Based on the results of the SWOT analysis using a SWOT analysis matrix, there are 4 strategy formulations based on strengths-opportunities, weaknesses-opportunities, strengths-threats, and weaknesses- threats. The recommended strategy in tourism development in Surakarta City during the Covid 19 pandemic is to increase community involvement, especially young people in tourism management and technology-based tourism development.